Multiple renal arteries with an ascending upward renal vein of the right kidney: A case report - Abdulrazzaq, Saad Mohammed (International Islamic University Malaysia, 2014)
As it is known; the majority of the human subjects has two renal arteries arising from the abdominal aorta; each will supply one kidney but in 30% of individuals, certain variations can be found. Accessory renal arteries constitute the most common and clinically important of these variations. For our case report, we are presenting one of these different variations that can be found in the blood supply of the kidneys. During dissecting the abdomen of an approximately 65 years-old male cadaver, multiple variations were found. There were double right renal arteries with prehilar branching of the upper renal artery. We found also that the right renal vein ascended upwards obliquely before ending in the lateral aspect of the inferior vena cava. Variation in the renal vessels is relatively common, especially multiple renal arteries, and can go smoothly without any abnormalities with the function of the kidney, but in some situations like renal transplantations, vascular reconstructions, and various surgical and radiological diagnostic techniques, the study of the anatomy of these variations is of crucial importance to decrease the patient morbidity during surgical procedures.